INTELLECTUAL-FACTORS AND PRINCIPLES OF CREATIVE TALENT DEVELOPMENT IN STUDENTS (American Journal of Interdisciplinary Research and Development, 2022)
The article focuses on the development of intellect and creative abilities in studentstirishgamini lit. Also, on the basis of the cluster approach, the scheme for the development ofualual-creative abilities in students is presented. The students are given a series of principles and systematic implementation of the work on the development of creative abilities.